THE OVERVIEW SURGICAL SITE INFECTION OF PASCA OPEN SURGICAL OF URINARY STONE AT ARIFIN ACHMAD GENERAL HOSPITAL OF RIAU PROVINCE 1 JANUARY – 31 DECEMBER 2014 PERIOD - M. Irvan Noorrahman; Dimas Pramita Nugraha; Afdal " (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2016)
ABSTRACTAbout 63% managemen urinary stone is open surgery, because this threatment choice could decrease the risk of recurency this disease but have the risk of high surgical site infection (SSI). This research explain about surgical site infection after open surgery of urinary stone in RSUD Arifin Achmad Province of Riau 1 January – 31 December period. The method of this research is retrospective descriptive. The source of data take from medical report of patient that undergo open surgery of urinary stone in RSUD Arifin Achmad Province of Riau. This research found 82 patient that undergo open surgery of urinary stone. The number of SSI in this research is 2,4% (2 patient). Based on the age group SSI found in the group 46-55 and 56-65 years old. Based on the gender SSI found more in women. Based on the nutrition SSI found in the group of under nutrition and normal nutrition. Based on level education SSI found in patient didn’t got education. Based on the preoperative diagnostic SSI found in patient with renal stone. Based on gift of the antibiotic prophilaxis SSI found in patient that gift the antibiotic prophilaxis. Based on the comorbid SSI found in patient with comorbid and without comorbid. Based on number of leukocytes SSI found in patient with normal and high leukocytes. Based on the named of surgery SSI found in pyelolitotomy and nephrolitotomy. Based on a duration of operative SSI found in the group with duration with 1 hour and >1 hour. Based on span of struck infection time SSI found more in >7 days. Based on a along of nursing SSI found in >3 hari. The conclution of this research is the number of SSI pasca open surgery of urinary stone in RSUD Arifin Achmad 1 January -31 December period is lower than the survey of World health organization (WHO).Key word : Surgical site infection, open surgery of urinary stone, discribe of patient